Epidemiologic and environmental characterization of the Re-emergence of St. Louis Encephalitis Virus in California, 2015-2020. - Mary E Danforth; Robert E Snyder; Tina Feiszli; Teal Bullick; Sharon Messenger; Carl Hanson; Kerry Padgett; Lark L Coffey; Christopher M Barker; William K Reisen; Vicki L Kramer (Public Library of Science (PLoS), 2022)
St. Louis encephalitis virus (SLEV) is an endemic flavivirus in the western and southeastern United States, including California. From 1938 to 2003, the virus was detected annually in California, but after West Nile virus (WNV) arrived in 2003, SLEV was not detected again until it re-emerged in Riverside County in 2015. The re-emerging virus in California and other areas of the western US is SLEV genotype III, which previously had been detected only in Argentina, suggesting a South American origin. This study describes SLEV activity in California since its re-emergence in 2015 and compares it to WNV activity during the same period. From 2015 to 2020, SLEV was detected in 1,650 mosquito pools and 26 sentinel chickens, whereas WNV was detected concurrently in 18,108 mosquito pools and 1,542 sentinel chickens from the same samples. There were 24 reported human infections of SLEV in 10 California counties, including two fatalities (case fatality rate: 8%), compared to 2,469 reported human infections of WNV from 43 California counties, with 143 fatalities (case fatality rate: 6%). From 2015 through 2020, SLEV was detected in 17 (29%) of California's 58 counties, while WNV was detected in 54 (93%). Although mosquitoes and sentinel chickens have been tested routinely for arboviruses in California for over fifty years, surveillance has not been uniform throughout the state. Of note, since 2005 there has been a steady decline in the use of sentinel chickens among vector control agencies, potentially contributing to gaps in SLEV surveillance. The incidence of SLEV disease in California may have been underestimated because human surveillance for SLEV relied on an environmental detection to trigger SLEV patient screening and mosquito surveillance effort is spatially variable. In addition, human diagnostic testing usually relies on changes in host antibodies and SLEV infection can be indistinguishable from infection with other flaviviruses such as WNV, which is more prevalent.